2012
DOI: 10.1002/cncr.27687
|View full text |Cite
|
Sign up to set email alerts
|

Is routine pelvic surveillance imaging necessary in patients with Wilms tumor?

Abstract: Background It is unclear if routine pelvic imaging is needed in patients with Wilms’ tumor. Thus, our primary objective examined the role of routine pelvic computed tomography (CT) in a cohort of pediatric patients with Wilms’ tumor. Methods With IRB approval we retrospectively identified 110 Wilms’ tumor patients diagnosed between January 1999 and December 2009; surveillance imaging continued through March 2011. We estimated survival (OS) and event-free survival (EFS), and dosimetry from dose length product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Low dose CT chest (1-2 mSV/scan) or abdomen might be able to detect smaller nodules but will increase the radiation burden and the value of routine CT surveillance is debated. 12,[23][24][25][26] Mortality rate was nearly twofold for patients presenting with clinical symptoms between planned surveillance compared to patients with asymptomatic relapse captured by planned surveillance visits. Despite this remarkable difference, the benefits of surveillance are less certain as the mortality difference may be due to other factors such as location of the tumour and tumour-specific growth rate ie, 'biological aggressiveness' as a confounding variable.…”
Section: Discussionmentioning
confidence: 99%
“…Low dose CT chest (1-2 mSV/scan) or abdomen might be able to detect smaller nodules but will increase the radiation burden and the value of routine CT surveillance is debated. 12,[23][24][25][26] Mortality rate was nearly twofold for patients presenting with clinical symptoms between planned surveillance compared to patients with asymptomatic relapse captured by planned surveillance visits. Despite this remarkable difference, the benefits of surveillance are less certain as the mortality difference may be due to other factors such as location of the tumour and tumour-specific growth rate ie, 'biological aggressiveness' as a confounding variable.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this is an important consideration for long term follow-up, MRI is not a risk-free long term strategy as evidenced by the recent concerns about the neurocognitive effects of general anaesthetic and the controversial issue of gadolinium accumulation in the deep white matter of the brain 21,22 . It has been shown that omitting the pelvis in follow-up CT studies can reduce the effective dose of the study by up to 45% without significant reduction in relapse detection 23,24 .…”
Section: Ctmentioning
confidence: 99%
“…Two studies focusing on children with sarcoma and rhabdomyosarcoma, respectively, showed that regular imaging studies neither facilitated earlier detection of recurrence nor improved overall survival . In Wilms tumor, routine surveillance CT scans of the pelvis were shown to be unnecessary, recommending substitution with abdominal ultrasound, and in patients with Neuroblastoma, CT scans seem to minimally contribute to detection of recurrences …”
Section: Discussionmentioning
confidence: 99%